أثر المرونة النفسية على جودة الحياة لدى عينة من الأخصائيين النفسانيين الممارسين بولاية الأغواط - مرية كركوري; تفاحة قجوح; خديجة دعماش (My University, 2023)
He current study aimed to find out "The impact of psychological flexibility on quality of life with a sample of practising psychologists, Where the descriptive curriculum is based, to collect data, the researchers used two measurements: The Sultan's Psychological Resilience Measure (2008) The Quality of life Measure prepared by Kazim and Forgotten (2006), their psychometric properties were confirmed on a sample of (30) practising psychologists, Practising psychologist, data processing and analysis Reliance on Statistical Program (SPSS 22) Through it, we have reached several conclusions: - There is no impact of psychological flexibility on the quality of life of the practising psychologist. - The psychological flexibility of the practising psychologist is high. - The level of quality of life of the practising psychologist is high. - There is no interaction between psychological flexibility and sex on the quality of life of the practising psychologist. - There is no interaction between psychological flexibility and the practising psychologist's quality of life experience